EFFECT OF FLUORIDE ON TOOTH ENAMEL - Temurova Dinara Temurovna; Zaripova Barno Ikramovna (Web of Journals Publishing, 2024)
Maintaining the integrity of tooth enamel is one of the main tasks of dentistry. This article discusses the effects of fluorides on tooth enamel.
Keywords: enamel, zinc, oral health, hydroxyapatite, fluoride, caries.